Pengaruh kualitas batu bara terhadap produksi gas SO2 dan NOx: studi kasus PLTU “Lentera” - Hermawan, Qori Fajar; Khoirunisa, Nanda; Sihotang, Zetsaona; Riza, Muhammad; Wasono, Wasono (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
The “Lentera” power plant is a 130 MW coal-fired power plant facility. The quality of the supplied coal to the “Lentera” power plant were tested using proximate and ultimate analysis to determine sulphur and nitrogen content. The production of SO2 and NOX emissions from coal combustion was affected by the sulphur and nitrogen content in the coal. Emission levels were observed using the Continuous Emission Monitoring System (CEMS). This research was conducted to determine the effect of the sulphur and nitrogen content in coal on the production of SO2 and NOX gas at